Phosphor powder method for producing

By controlling the Si/Al molar ratio and calcination conditions, the method improves the luminescent properties and total luminous flux of SCASN phosphor powder, enhancing its suitability for LED applications.

JP2025018510APending Publication Date: 2025-02-06DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023122267
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Existing methods for manufacturing SCASN phosphors exhibit room for improvement in luminescent properties, particularly in terms of luminescent efficiency and emission spectrum width.

Method used

A method for producing phosphor powder with a specific Si/Al molar ratio of 0.85 to 1.0, calcination under inert gas at 1500°C to 2100°C, and particle size control to less than 5 μm, resulting in improved luminescent properties and reduced emission peak half-width.

Benefits of technology

The method enhances the total luminous flux and luminescent properties of the phosphor powder, making it suitable for applications in LED packages, mini LEDs, and micro LEDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018510000001
    Figure 2025018510000001
Patent Text Reader

Abstract

To provide a method for producing phosphor powder having excellent light-emitting properties.SOLUTION: A method for producing phosphor powder that includes a phosphor in which a main crystal phase has a crystal structure same as CaAlSiN3, and which is expressed by general formula (Ca1-x-ySrxEuy) AlSiN3 (note that 0≤x<1, 0<y<1, 1-x-y>0) includes: a mixing step of mixing raw material powder to obtain mixed raw material powder; and a calcination step of calcinating the obtained mixed raw material powder. In the mixing step, Si / Al ratio of the mixed raw material powder is 0.85 or more and less than 1.0 on molar basis, and a particle diameter (D50) at a point where a cumulative volume from a smaller particle side reaches 50% of phosphor powder to be obtained is 5 μm or less, in volume frequency grain size distribution measured by a laser diffraction scattering method.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a phosphor powder. [Background technology]

[0002] In order to manufacture white LEDs, research has been conducted into red phosphors that convert blue light from a blue LED chip into red light. Known red phosphors include CASN phosphors such as CASN phosphor and SCASN phosphor (for example, Patent Document 1, etc.). These CASN phosphors are generally synthesized by heating raw material powders that include europium oxide or europium nitride, calcium nitride, silicon nitride, and aluminum nitride. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2005 / 052087 Summary of the Invention [Problem to be solved by the invention]

[0004] However, as a result of investigations by the present inventors, it was found that the method for producing the SCASN phosphor described in Patent Document 1 above leaves room for improvement in terms of the light emitting properties of the phosphor powder. [Means for solving the problem]

[0005] As a result of further investigation, the inventors have found that a method for producing a phosphor powder in which a raw material powder mixture having a Si / Al ratio in molar terms of 0.85 or more and less than 1.0 is sintered can improve the total luminous flux when the resulting phosphor powder is mixed with a resin and formed into a sheet, thereby completing the present invention.

[0006] According to one aspect of the present invention, there is provided the following method for producing a phosphor powder.

[0007] 1. The main crystal phase has the same crystal structure as CaAlSiN3 and has the general formula (Ca 1-x-y Sr x EU y )AlSiN3, 0≦x<1, 0 <y<1、1-x-y> A method for producing a phosphor powder containing a phosphor having a molecular weight of 0, a mixing step of mixing the raw material powders to obtain a raw material mixed powder; A firing step of firing the obtained raw material mixed powder, In the mixing step, the Si / Al ratio of the raw material mixed powder is equal to or greater than 0.85 and less than 1.0 in terms of moles, A method for producing a phosphor powder, wherein the particle diameter (D50) of the resulting phosphor powder at the point where the cumulative volume from the small particle side is 50% in a volume frequency particle size distribution measured by a laser diffraction scattering method is 5 μm or less. 2. A method for producing the phosphor powder according to 1., comprising the steps of: A method for producing a phosphor powder, in which the emission spectrum emitted when the obtained phosphor powder is irradiated with light having a wavelength of 455 nm has a half-value width of an emission peak in the wavelength range of 465 to 800 nm of less than 90.0 nm. 3. A method for producing a phosphor powder according to any one of 1. to 3., The method for producing a phosphor powder, wherein the firing step is performed in an inert gas atmosphere of 10 MPa or less. 4. A method for producing a phosphor powder according to any one of 1. to 4., The method for producing phosphor powder, wherein the firing in the firing step is carried out at a temperature of 1500° C. or higher and 2100° C. or lower. 5. A method for producing a phosphor powder according to any one of 1. to 5., The method for producing a phosphor powder, wherein the firing in the firing step is carried out for 0.5 hours or more and 30 hours or less. Effect of the Invention

[0008] According to the present invention, there is provided a method for producing phosphor powder having excellent luminescence characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The method for producing the phosphor powder of this embodiment will be outlined below.

[0010] The method for producing a phosphor powder containing the phosphor of this embodiment includes a mixing step of mixing raw material powders to obtain a raw material mixed powder, and a firing step of firing the obtained raw material mixed powder, in which the Si / Al ratio of the raw material mixed powder in the mixing step satisfies a value of 0.85 or more and less than 1.0 in molar terms. The phosphor powder obtained by this method has a main crystal phase having the same crystal structure as CaAlSiN3 and has the general formula (Ca 1-x-y Sr x EU y )AlSiN3(where 0≦x<1, 0 <y<1、1-x-y> 0) is included. In addition, in the volume frequency particle size distribution of the phosphor powder obtained by this manufacturing method measured by a laser diffraction scattering method, the particle diameter (D50) at the point where the cumulative volume from the small particle side is 50% is 5 μm or less.

[0011] According to the findings of the present inventors, it has been found that by producing a phosphor powder by firing a raw material powder mixture having a Si / Al ratio of 0.85 or more and less than 1.0 in molar terms, the total luminous flux can be improved when the obtained phosphor powder is mixed with a resin and formed into a sheet. Although the detailed mechanism is unclear, it is believed that by making the Si / Al ratio of the raw material powder mixture less than 1.0, the production of by-products with a large half-width of the emission spectrum can be suppressed, thereby improving the luminescence characteristics of the phosphor powder. On the other hand, by setting the Si / Al ratio of the raw material mixed powder to 0.85 or more, the desired SCASN phosphor can be stably produced, and it is considered that the luminescence characteristics of the phosphor powder can be improved.

[0012] In the emission spectrum emitted when the phosphor powder is irradiated with light having a wavelength of 455 nm, the half width of the emission peak in the wavelength range of 465 to 800 nm is, for example, less than 90.0 nm, preferably 89.9 nm or less, more preferably 89.8 nm or less, thereby further improving the light emitting properties of the phosphor powder.

[0013] The phosphor powder obtained by the manufacturing method of this embodiment has good luminescence characteristics both when in powder form and when mixed with a resin to form a sheet, and is therefore suitable for a variety of uses. One example of the application is an LED package, in which the phosphor powder of the present invention is used as a wavelength conversion material for converting blue light emitted from a blue LED into white light. Another example application could be in self-emissive displays such as mini-LEDs and micro-LEDs.

[0014] Each step of the method for producing the phosphor powder of this embodiment will be described in detail below.

[0015] The method for producing the phosphor powder of this embodiment preferably includes the following steps. A mixing process in which the starting materials are mixed to obtain a raw material powder mixture. A firing process in which the raw material powder obtained in the mixing process is fired to obtain a fired product.

[0016] Incidentally, in this embodiment, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.

[0017] ·Mixing process In the mixing step, the starting materials (raw material powders) are mixed to obtain a raw material mixed powder. Examples of the starting material include raw material powder containing Al, raw material powder containing Si, raw material powder containing Sr (when x≠0), raw material powder containing Ca, and raw material powder containing Eu. The above starting materials are preferably in the form of powder.

[0018] As the raw material powder containing Al, an aluminum compound such as aluminum nitride can be used. As the raw material powder containing Si, silicon nitride such as α-type silicon nitride can be used. As the raw material powder containing Sr, a strontium compound such as strontium nitride can be used. As the Ca-containing raw material powder, a calcium compound such as calcium nitride can be used. As the raw material powder containing Eu, a europium compound can be used. The starting material is not limited to these, and nitrides or oxides containing the elements that constitute the phosphor can be used.

[0019] Examples of europium compounds include oxides containing europium, hydroxides containing europium, nitrides containing europium, oxynitrides containing europium, and halides containing europium. These can be used alone or in combination of two or more. Among these, it is preferable to use europium oxide, europium nitride, and europium fluoride alone, and it is more preferable to use europium oxide alone.

[0020] A raw material containing Si and a raw material containing Al are used so that the molar ratio of Si to Al in the SCASN phosphor after firing is 0.85 or more and less than 1.0, preferably 0.85 or more and 0.99 or less, and more preferably 0.85 or more and 0.975 or less.

[0021] In the mixing step, the raw material mixed powder can be obtained, for example, by a method of dry mixing the starting materials, or a method of wet mixing in an inert solvent that does not substantially react with each starting material, followed by removing the solvent. As a mixing device, for example, a small mill mixer, a V-type mixer, a rocking mixer, a ball mill, a vibration mill, etc. can be used. After mixing using the device, the raw material mixed powder can be obtained by removing aggregates using a sieve as necessary. In order to prevent deterioration of the starting materials and unintended inclusion of oxygen, the mixing step is preferably carried out in a nitrogen atmosphere and in an environment with as little moisture (humidity) as possible.

[0022] · Firing process In the firing step, the raw material powder mixture obtained in the mixing step is fired to obtain a fired product. The firing temperature in the firing step is not particularly limited, but is preferably 1500°C or higher and 2100°C or lower, and more preferably 1550°C or higher and 2000°C or lower. By setting the firing temperature to the above lower limit or higher, the grain growth of the phosphor particles proceeds more effectively, thereby making it possible to further improve the light absorptance, internal quantum efficiency, and external quantum efficiency. By setting the firing temperature to the above upper limit or lower, the decomposition of the phosphor particles can be further suppressed. Therefore, the light absorption rate, the internal quantum efficiency, and the external quantum efficiency can be further improved. In addition, excessive growth of the phosphor particles can be suppressed, and the D of the phosphor powder can be further improved. 50 It becomes possible to control the value to a desired value or less. Other conditions in the firing step, such as the temperature rise time, temperature rise rate, heating retention time, and pressure, are not particularly limited and may be appropriately adjusted depending on the raw materials used. Typically, the heating retention time is preferably 0.5 hours or more and 30 hours or less, and the pressure is preferably 0.1 MPa or more and 10 MPa or less. The firing step is preferably carried out in an inert gas atmosphere such as a nitrogen gas atmosphere from the viewpoint of controlling the oxygen concentration, etc. As a specific example, the firing step is preferably carried out in a nitrogen gas atmosphere at a pressure of 0.1 MPa or more and 10 MPa or less.

[0023] In the firing step, the firing method may be, for example, a method in which the mixture is filled into a container made of a material (such as tungsten) that does not react with the mixture during firing, and the container is heated in a nitrogen atmosphere.

[0024] The fired product obtained through the firing step is usually a granular or lumpy sintered body. The fired product can be powdered once by using a process such as crushing, grinding, or classification, either alone or in combination. A specific processing method includes, for example, pulverizing the sintered body to a predetermined particle size using a general pulverizer such as a ball mill, a vibration mill, a jet mill, etc. However, it should be noted that excessive pulverization may generate fine particles that easily scatter light or may cause crystal defects on the particle surface, resulting in a decrease in luminous efficiency.

[0025] In addition to the above-mentioned mixing and firing steps, the method for producing the phosphor powder of this embodiment may, if necessary, include one or more steps selected from the group consisting of a low-temperature firing step, a grinding step, a decantation step, a filtration / drying step, and an acid treatment step.

[0026] Low-temperature firing process (annealing process) The method for producing the phosphor powder of this embodiment may include a low-temperature firing step (annealing step) after the firing step, if necessary. In the low-temperature firing step, the fired product is heated at a temperature lower than the firing temperature in the firing step. The fired product used in the low-temperature firing step may be from any step, for example, immediately after the firing step or immediately after the crushing step.

[0027] The low-temperature firing step (annealing step) is preferably carried out in a non-oxidizing atmosphere other than pure nitrogen, such as an inert gas such as a rare gas or nitrogen gas, a reducing gas such as hydrogen gas, carbon monoxide gas, hydrocarbon gas, or ammonia gas, or a mixture of these gases, or in a vacuum, etc. It is particularly preferably carried out in a hydrogen gas atmosphere or an argon atmosphere.

[0028] The low-temperature firing step (annealing step) may be performed under atmospheric pressure or under pressure. The heat treatment temperature in the low-temperature firing step (annealing step) is not particularly limited, but is preferably 1200° C. to 1700° C., more preferably 1300° C. to 1600° C. The time for the low-temperature firing step (annealing step) is not particularly limited, but is preferably 3 hours to 12 hours, more preferably 5 hours to 10 hours. By performing a low-temperature firing process (annealing process), the luminous efficiency of the phosphor particles can be sufficiently improved. In addition, the rearrangement of elements removes distortions and defects, which improves transparency.

[0029] Crushing process The method for producing the phosphor powder of this embodiment may include a pulverization step after the firing step, if necessary. In the pulverization step, the fired product is pulverized to obtain fine powder. The fired product used in the pulverization step may be from any step, for example, immediately after the firing step or immediately after the low-temperature firing step.

[0030] The crushing step is preferably carried out using a ball mill. It is preferable to carry out the treatment using the method shown below. If the treatment is carried out outside the range of conditions, the performance of the phosphor particles cannot be maintained. If the crushing force is too strong, defects will be generated in the phosphor particles, degrading the optical properties. If the crushing force is too weak, the desired fineness cannot be achieved.

[0031] In the pulverization step, a ball mill is preferably used as a pulverizer, and the pulverization step is desirably performed by ball mill pulverization in a wet manner in the presence of an aqueous solution such as ion-exchanged water.

[0032] The aqueous solution may contain components other than ion-exchanged water, such as organic solvents, such as lower alcohols and acetone, and dispersants, such as sodium hexametaphosphate, sodium pyrophosphate (Napp), trisodium phosphate (TSP), and surfactants.

[0033] The lower limit of the amount of the aqueous solution may be, for example, 0.1% by volume or more, 0.3% by volume or more, 0.5% by volume or more, or 1.0% by volume or more based on the total volume of the annealed product. By setting the lower limit of the amount of the aqueous solution within the above range, the annealed product can be pulverized under milder conditions, and the deterioration of the optical properties as a phosphor can be further suppressed. The upper limit of the amount of the aqueous solution may be, for example, 60% by volume or less, 50% by volume or less, 45% by volume or less, or 40% by volume or less based on the total volume of the annealed product. By setting the upper limit of the amount of the aqueous solution within the above range, the force applied to the pulverization of the annealed product by the ball can be improved. The amount of the aqueous solution may be adjusted within the above range, and may be, for example, 1.0 to 45% by volume based on the total volume of the annealed product.

[0034] Zirconia balls can be used as balls for use in the ball mill. The diameter of the balls may be, for example, 0.2 to 20.0 mm, or 0.5 to 10.0 mm. Outside these conditions, it is difficult to keep the average circularity and the standard deviation of the circularity within the specified range, and it is difficult for the resulting phosphor powder to exhibit the desired color reproducibility.

[0035] The lower limit of the time of the pulverization treatment (pulverization time) in the pulverization step may be, for example, 1 hour or more, 2 hours or more, 3 hours or more, 4 hours or more, 5 hours or more, 6 hours or more, 7 hours or more, 8 hours or more, 9 hours or more, 10 hours or more, or 12 hours or more. By setting the lower limit of the pulverization time within the above range, a sufficiently fine pulverized product can be obtained, and the efficiency of the acid treatment in the subsequent acid treatment step can be further improved. The upper limit of the time of the pulverization treatment may be, for example, 80 hours or less, 70 hours or less, 60 hours or less, or 40 hours or less. By setting the upper limit of the pulverization time within the above range, it is possible to more sufficiently suppress the occurrence of scratches and cracks on the surface of the phosphor particles, and the occurrence of defects inside the phosphor particles, caused by excessive pulverization of the annealed product. The pulverization time may be adjusted within the above range, and may be, for example, 1 to 60 hours, or 4 to 40 hours.

[0036] Decantation process The method for producing the phosphor powder of this embodiment may include a decantation step, if necessary. In the decantation step, ultrafine powder contained in the fired product is removed. The fired product used in the pulverization step may be from any step, for example, immediately after the firing step, immediately after the low-temperature firing step, or immediately after the pulverization step.

[0037] In the decantation step, the powdered fired product (phosphor particles) is put into an appropriate dispersion medium and dispersed. The dispersion medium may be, for example, an aqueous solution containing sodium hexametaphosphate, sodium pyrophosphate (Napp), trisodium phosphate (TSP), lower alcohol, acetone, a surfactant, etc. In this case, the weight ratio of the phosphor particles to the dispersion medium is preferably 2% or more and 40% or less, more preferably 3% or more and 20% or less, and even more preferably 4% or more and 10% or less. Next, after the dispersion treatment, the dispersion medium containing the phosphor particles is left to stand or centrifuged to allow the particles to settle. Subsequently, the particles are allowed to settle, and the supernatant is removed. This makes it possible to remove fine particles (ultrafine powder) contained in the supernatant that may adversely affect optical properties. In addition, aggregation due to ultrafine powder is reduced. The particle diameter of the fine particles (ultrafine powder) is, for example, less than 0.4 μm.

[0038] · Filtration and drying process The method for producing the phosphor powder of this embodiment may include a filtering and drying step after the firing step, if necessary. The calcined product used in the filtration and drying step may be, for example, the product immediately after the calcination step, or the product immediately after any step carried out after the calcination step. Specifically, the precipitate obtained in the decantation step may be filtered and dried. After the filtering and drying process, coarse particles may be removed using a sieve if necessary. This reduces fine particles (ultrafine powder) and allows the desired phosphor particles to be obtained. For drying, a tray dryer, freeze drying, supercritical drying, vacuum drying, fluidized bed dryer, far-infrared dryer, microwave dryer, spray dryer, etc. may be used. In addition, a dispersant or the like may be added to suppress aggregation before drying.

[0039] Acid treatment process The method for producing the phosphor powder of this embodiment may include an acid treatment step after the firing step, if necessary. In the acid treatment step, the calcined product is treated with acid. The calcined product used in the acid treatment step may be, for example, a product immediately after the calcination step, or a product immediately after any step carried out after the calcination step. By treating the fired product with an acid, it is possible to remove at least a portion of the impurities that do not contribute to light emission. Incidentally, it is presumed that the impurities that do not contribute to light emission are generated during the firing process or the low-temperature firing process (annealing process).

[0040] The acid may be an aqueous solution containing one or more acids selected from hydrofluoric acid, sulfuric acid, phosphoric acid, hydrochloric acid, and nitric acid. In particular, hydrofluoric acid, nitric acid, and a mixed acid of hydrofluoric acid and nitric acid are preferred. The acid treatment can be carried out by dispersing the low-temperature calcined powder in an aqueous solution containing the above-mentioned acid. The stirring time is, for example, from 10 minutes to 6 hours, preferably from 30 minutes to 3 hours. The stirring temperature can be, for example, from 40°C to 90°C, preferably from 50°C to 70°C. After the acid treatment step, it is preferable to separate substances other than the phosphor particles by filtration and to wash the substances adhering to the phosphor particles with water.

[0041] (About phosphors) The phosphor contained in the phosphor powder obtained by the method for producing phosphor powder of this embodiment may include a CASN phosphor and / or a SCASN phosphor. Each of the CASN phosphor and the SCASN phosphor has a crystal structure in which the main crystal phase is CaAlSiN3, and has the general formula (Ca 1-x-y Sr x EU y)AlSiN3(where 0≦x<1, 0 <y<1、1-x-y> It has the composition: A representative phosphor that approximates the above general formula is CaAlSiN3, where the Ca site occupancy is 100% and Si / Al=1. 2+ A part of Eu acts as a luminescence center. 2+ When substituted with , it becomes a red-emitting phosphor. Such phosphors are often called "CASN", an acronym for the elements. Another phosphor is (Sr,Ca)AlSiN3, in which Sr is substituted for Ca and dissolved in solid solution. 2+ A part of Eu acts as a luminescence center. 2+ When substituted with , it becomes a red-emitting phosphor. Such phosphors are often referred to as "SCASN", an acronym for the elements.

[0042] D of the phosphor powder obtained by the manufacturing method of this embodiment 50 The upper limit of the (median diameter) is 5 μm or less, more preferably 4.8 μm or less, and further preferably 4.5 μm or less. 50 Since the diameter is not too large or too small, the total luminous flux can be improved when the phosphor powder is formed into a sheet, making it suitable for use in mini LEDs or micro LEDs, for example. Although the detailed mechanism is unclear, it is speculated that if the particle size is too large, gaps will form between the particles in the sheet (sheet-shaped molded body), and the excitation light will pass through these gaps, lowering the sheet's absorption rate, i.e., the total luminous flux will also decrease. 50 It is believed that by using a phosphor powder having the above formula, the gaps between particles in the sheet can be narrowed, and as a result, a decrease in the total luminous flux of the sheet can be suppressed. On the other hand, the D of the phosphor powder 50 The lower limit is not particularly limited, but is preferably 0.1 μm or more, and more preferably 0.3 μm or more.

[0043] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES

[0044] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.

[0045] <Method of manufacturing phosphor powder> Example 1 In a glove box maintained under a nitrogen atmosphere, 22.6 parts by mass of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 23.3 parts by mass of aluminum nitride (AlN, manufactured by Tokuyama Corporation, E grade), 2.5 parts by mass of calcium nitride (Ca3N2, manufactured by Materion), 45.7 parts by mass of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.), and 6.0 parts by mass of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd., RU grade) were weighed out and placed in a container and dry-mixed to obtain a raw material powder (mixed powder). In a glove box, the raw material powder was filled into a tungsten container with a lid. The container with the lid was removed from the glove box and placed in an electric furnace equipped with a carbon heater, and then the pressure in the electric furnace was sufficiently evacuated until it reached 0.1 PaG or less. The temperature in the electric furnace was raised to 850°C while continuing the evacuation. After reaching 850°C, nitrogen gas was introduced into the electric furnace and the pressure in the electric furnace was adjusted to 0.025 MPaG. Then, in a nitrogen gas atmosphere, the temperature in the electric furnace was raised to 1550°C, and after reaching the temperature, the heat treatment was performed for 4 hours while maintaining the temperature. Then, the heating was terminated and the material was cooled to room temperature. After cooling to room temperature, the lumps were collected from the container. The collected lumps were crushed and pulverized to obtain a sintered powder. The obtained fired powder was placed in a ball mill and subjected to wet grinding treatment for 4 hours to prepare a ground product (grinding step). Zirconia balls with a diameter of 3 mm were used as the balls. A red phosphor powder was obtained as the ground product.

[0046] Example 2 A phosphor powder was obtained in the same manner as in Example 1, except that the amounts of raw materials used were as follows: In a glove box maintained under a nitrogen atmosphere, 23.6 parts by mass of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 23.0 parts by mass of aluminum nitride (AlN, manufactured by Tokuyama Corporation, E grade), 2.5 parts by mass of calcium nitride (Ca3N2, manufactured by Materion), 45.1 parts by mass of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.), and 5.9 parts by mass of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd., RU grade) were weighed out and placed in a container and dry-mixed to obtain a raw material powder (mixed powder).

[0047] Example 3 A phosphor powder was obtained in the same manner as in Example 1, except that the amounts of raw materials used were as follows: In a glove box maintained under a nitrogen atmosphere, 24.6 parts by mass of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 22.7 parts by mass of aluminum nitride (AlN, manufactured by Tokuyama Corporation, E grade), 2.5 parts by mass of calcium nitride (Ca3N2, manufactured by Materion), 44.5 parts by mass of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.), and 5.8 parts by mass of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd., RU grade) were weighed out and placed in a container and dry-mixed to obtain a raw material powder (mixed powder).

[0048] Example 4 A phosphor powder was obtained in the same manner as in Example 1, except that the amounts of raw materials used were as follows: In a glove box maintained under a nitrogen atmosphere, 25.0 parts by mass of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 22.5 parts by mass of aluminum nitride (AlN, manufactured by Tokuyama Corporation, E grade), 2.4 parts by mass of calcium nitride (Ca3N2, manufactured by Materion), 44.2 parts by mass of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.), and 5.8 parts by mass of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd., RU grade) were weighed out and placed in a container and dry-mixed to obtain a raw material powder (mixed powder).

[0049] Comparative Example 1 A phosphor powder was obtained in the same manner as in Example 1, except that the amounts of raw materials used were as follows: In a glove box maintained under a nitrogen atmosphere, 25.5 parts by mass of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 22.4 parts by mass of aluminum nitride (AlN, manufactured by Tokuyama Corporation, E grade), 2.4 parts by mass of calcium nitride (Ca3N2, manufactured by Materion), 43.9 parts by mass of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.), and 5.8 parts by mass of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd., RU grade) were weighed out and placed in a container and dry-mixed to obtain a raw material powder (mixed powder).

[0050] Comparative Example 2 A phosphor powder was obtained in the same manner as in Example 1, except that the amounts of raw materials used were as follows: In a glove box maintained under a nitrogen atmosphere, 21.5 parts by mass of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 23.6 parts by mass of aluminum nitride (AlN, manufactured by Tokuyama Corporation, E grade), 2.6 parts by mass of calcium nitride (Ca3N2, manufactured by Materion), 46.3 parts by mass of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.), and 6.1 parts by mass of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd., RU grade) were weighed out and placed in a container and dry-mixed to obtain a raw material powder (mixed powder).

[0051] Comparative Example 3 A phosphor powder was obtained in the same manner as in Example 1, except that the amounts of raw materials used were as follows: In a glove box maintained under a nitrogen atmosphere, 20.5 parts by mass of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 23.9 parts by mass of aluminum nitride (AlN, manufactured by Tokuyama Corporation, E grade), 2.6 parts by mass of calcium nitride (Ca3N2, manufactured by Materion), 46.9 parts by mass of strontium nitride (Sr3N2, purity 2N, manufactured by Kojundo Chemical Laboratory Co., Ltd.), and 6.2 parts by mass of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd., RU grade) were weighed out and placed in a container and dry-mixed to obtain a raw material powder (mixed powder).

[0052] Comparative Example 4 A phosphor powder was obtained in the same manner as in Example 2, except that the firing temperature was 1930°C.

[0053] <Confirmation of crystal structure> The crystal structure of the phosphor powders obtained in each of the Examples and Comparative Examples was confirmed by the powder X-ray diffraction pattern using Cu-Kα radiation using an X-ray diffractometer (Ultima IV manufactured by Rigaku Corporation). As a result, the powder X-ray diffraction pattern of the phosphor powders obtained in each of the Examples and Comparative Examples was confirmed to have the same diffraction pattern as CaAlSiN3 crystals. In other words, it was confirmed that the phosphor particles contained in the phosphor powders of each of the Examples and Comparative Examples have the same crystal structure as CaAlSiN3 in the main crystal phase.

[0054] [Table 1]

[0055] The phosphor powder obtained above was evaluated for the following items.

[0056] <Measurement of absorptivity, emission peak wavelength, and half-width for 455 nm light> The absorptance of each of the phosphor powders obtained in Examples 1 to 4 and Comparative Examples 1 to 4 when irradiated with excitation light having a wavelength of 455 nm was calculated by the following procedure. The results are shown in Table 1.

[0057] First, the phosphor powder to be measured was filled into a concave cell so that the surface was smooth, and the cell was attached to the opening of the integrating sphere. Monochromatic light with a wavelength of 455 nm was split from a Xe lamp, which was a light source, and introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. The phosphor powder to be measured was irradiated with this monochromatic excitation light, and the fluorescence spectrum was measured. A spectrophotometer (manufactured by Otsuka Electronics Co., Ltd., product name: MCPD-7000) was used for the measurement.

[0058] From the obtained fluorescence spectrum data, the number of reflected excitation light photons (Qref) and the number of fluorescent photons (Qem) were calculated. The number of reflected excitation light photons was calculated in the same wavelength range as the number of excitation light photons, and the number of fluorescent photons was calculated in the range of 465 to 800 nm. In addition, using the same device, a standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At that time, the number of excitation light photons (Qex) was calculated from the spectrum in the wavelength range of 450 to 465 nm.

[0059] From the above calculation results, the absorptance of the 455 nm excitation light of the phosphor powder to be measured was calculated based on the following formula. Absorption rate of 455 nm excitation light = ((Qex-Qref) / Qex) x 100

[0060] The emission peak wavelength of the phosphor powder was determined to be the wavelength that showed the highest intensity in the wavelength range of 465 to 800 nm in the spectrum data obtained by attaching the phosphor powder to the opening of the integrating sphere.

[0061] <Particle size measurement> The particle size distribution of the phosphor powder was measured using the following procedure using a particle size measuring device, Microtrac MT3300EXII (Microtrac Bell Co., Ltd.), which uses the laser diffraction and scattering method. From the particle size distribution obtained, the particle size D50 (μm) corresponding to the cumulative 50% in the volume-based integrated fraction was calculated. The ultrasonic homogenizer used was "US-150E" (manufactured by Nippon Seiki Co., Ltd.). (Processing) 30 mg of phosphor powder was uniformly dispersed in 100 ml of 0.2% sodium hexametaphosphate aqueous solution, and the resulting dispersion was placed in a cylindrical container with an inner diameter of 5.5 cm at the bottom. Next, the transducer (cylindrical tip with an outer diameter of 20 mm) of an ultrasonic homogenizer was inserted from above the dispersion, and with the transducer immersed to a depth of 1.0 cm or more, ultrasonic waves were irradiated to the dispersion for 3 minutes at a frequency of 19.5 kHz and an output of 150 W.

[0062] <Measurement of total luminous flux for a cured resin sheet with phosphor powder dispersed in it> [Preparation of cured resin sheet (measurement sample)] First, 40 parts by mass of the phosphor powder to be measured and 60 parts by mass of silicone resin (manufactured by Toray Dow Corning Co., Ltd., product name: OE-6630) were mixed and degassed using a rotation / revolution mixer to obtain a uniform mixture (liquid). Next, the mixture was dropped onto a transparent first fluororesin film, and a transparent second fluororesin film was further layered on top of the dropped matter to obtain a sheet-like laminate. The sheet-like laminate was then formed into an uncured sheet by adjusting the thickness of the layer of the dropped matter using a roller with a gap of 50 μm added to the total thickness of the first fluororesin film and the second fluororesin film.

[0063] The uncured sheet was heat-treated at 150° C. for 60 minutes. After the heat treatment, the first fluororesin film and the second fluororesin film were peeled off to obtain a cured resin sheet having a thickness of 50±5 μm and having the phosphor dispersed therein.

[0064] [Total luminous flux measurement] A blue light emitting diode (blue LED) having a peak wavelength in the range of 450 to 460 nm was prepared. The blue light emitted from the blue LED was irradiated onto one main surface of the resin cured sheet, and the emission spectrum of the light emitted from the other main surface of the resin cured sheet was measured. The total luminous flux was calculated from the spectral data in the wavelength range of 500 to 800 nm of the emission spectrum. The evaluation results were relative evaluations in which the total luminous flux produced using the phosphor of Comparative Example 1 was taken as 100%. The results are shown in Table 1.

[0065] The blue light emitting diode used in the measurement had a peak wavelength of 450 to 460 nm, a chromaticity X of 0.145 to 0.165, and a chromaticity Y of 0.023 to 0.037 (product number: SMT type, PLCC-6, 0.2 W, SMD 5050 LED).

[0066] The phosphor powders of Examples 1 to 4 showed higher total luminous flux values ​​when used as a sheet than those of Comparative Examples 1 to 4. The phosphor powders of such examples are preferably applicable to mini LEDs or micro LEDs.

Claims

1. The main crystal phase is CaAlSiN 3 and has the same crystal structure as that of the general formula (Ca 1-x-y Sr x EU y ) AlSiN 3 A method for producing a phosphor powder containing a phosphor represented by the formula: a mixing step of mixing the raw material powders to obtain a raw material mixed powder; A firing step of firing the obtained raw material mixed powder, In the mixing step, the Si / Al ratio of the raw material mixed powder is equal to or greater than 0.85 and less than 1.0 in terms of moles, A method for producing a phosphor powder, wherein the particle diameter (D50) of the obtained phosphor powder at the point where the cumulative volume from the small particle side is 50% in a volume frequency particle size distribution measured by a laser diffraction scattering method is 5 μm or less.

2. A method for producing the phosphor powder according to claim 1, The method for producing a phosphor powder has an emission spectrum when the obtained phosphor powder is irradiated with light having a wavelength of 455 nm, and the half-width of the emission peak in the wavelength range of 465 to 800 nm is less than 90.0 nm.

3. A method for producing a phosphor powder according to claim 1 or 2, comprising the steps of: The method for producing a phosphor powder, wherein the firing step is performed in an inert gas atmosphere of 10 MPa or less.

4. A method for producing a phosphor powder according to claim 1 or 2, comprising the steps of: The method for producing a phosphor powder, wherein the firing in the firing step is performed at 1500° C. or higher and 2100° C. or lower.

5. A method for producing a phosphor powder according to claim 1 or 2, comprising the steps of: The method for producing a phosphor powder, wherein the firing in the firing step is carried out for 0.5 hours or more and 30 hours or less.

Citation Information

Patent Citations

  • Phosphor, and phosphor-containing composition and light-emitting device using the phosphor, and illuminating device and image display device using the light-emitting device

    JP2014227454A

  • Production method of nitride phosphor

    JP2014240465A

  • Method of producing phosphor powder

    JP2023082287A

  • Phosphor and light emitting device

    WO2015002139A1

  • Fluorescent body and light-emitting device

    WO2020054351A1